2020
DOI: 10.1097/prs.0000000000006888
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Assessment of DIEP Flap Breast Reconstruction Using Indocyanine Green Angiography: Reduction of Fat Necrosis, Resection Volumes, and Postoperative Surveillance

Abstract: Background: This study aims to characterize the effect of laser-assisted indocyanine green fluorescence angiography on fat necrosis and flap failure in deep inferior epigastric artery perforator (DIEP) flap breast reconstruction. Methods: A retrospective review was performed on 1000 free flaps for breast reconstruction at a single center from 2010 to 2017. Indocyanine green angiography was used after completion of recipient-site anastomoses to subjectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 29 publications
1
50
0
4
Order By: Relevance
“…There were no clinical signs of fat necrosis in this series. All flaps were evaluated with indocyanine green 15 at time of inset. Intraoperative details and postoperative course is shown in Tables 2 and 3 .…”
Section: Resultsmentioning
confidence: 99%
“…There were no clinical signs of fat necrosis in this series. All flaps were evaluated with indocyanine green 15 at time of inset. Intraoperative details and postoperative course is shown in Tables 2 and 3 .…”
Section: Resultsmentioning
confidence: 99%
“…A similar reduction in FN (from 71% to 0%) was described by Casey et al (2015) 19 , and in a randomized controlled trial by Varela et al ( 2020) 18 (from 59% to 8.3%). Hembd et al (2020) 22 recently demonstrated that use of NIRF was associated with a decrease in the odds of developing FN (OR, 0.38; p=0.004). Taken together, reported incidence of FN in the above mentioned studies was variable (0%-71%).…”
Section: Discussionmentioning
confidence: 99%
“…While patients with a thicker abdominal fat pad may be at increased risk for flap fat necrosis, intraoperative precautions may improve outcomes. Among these are increasing the number of perforators the flap is based on as well as using intraoperative tools such as indocyanine green angiography to assess flap perfusion, which have previously been shown to reduce fat necrosis occurrence rates (Hembd et al, 2020; Malagón‐López et al, 2019; Momeni & Sheckter, 2020).…”
Section: Discussionmentioning
confidence: 99%